A new wilderness for Central Europe? — The potential for large strictly protected forest reserves in Germany. (September 2019) - Brackhane, Sebastian; Schoof, Nicolas; Reif, Albert; Schmitt, Christine B.
Abstract: The German National Strategy on Biological Diversity (NBS) aims to establish wilderness areas on 2% of the German terrestrial territory by 2020, however wilderness areas in Germany currently only cover 0.6% of the total land area. Operationalizing the wilderness concept in densely populated countries like Germany where few primary habitats remain is challenging. In this study, we developed minimum criteria (including fragmentation, compactness and size) for forest wilderness areas and assessed their number, spatial distribution and extent for Germany. We tested their ecological representativeness in the main German ecoregions, their compatibility with ecological networks, overlaps with existing protected areas, and forest ownership. Our results revealed a potential for forest wilderness areas to cover 10.3% of the German terrestrial territory for candidate sites ≥1000 ha, which is reduced to 4.1% and 0.6% when applying larger minimum sizes (3000 ha; 10, 000 ha). Candidate sites of ≥10, 000 ha were restricted to mountainous regions ( n = 12) and the less populated Northeast German Plain ( n = 4). Forest ownership and protected areas designated to protect cultural landscapes further limit this potential. Our study is a first step toward the systematic planning for wilderness areas in Germany. It shows the country's potential to achieve its wilderness goals, if criteria are adapted to high infrastructure densities and rely on developing wilderness in currently used forests. Considering the number of forest areas that extend over national borders, concerted efforts at the European level could lead toward ecologically valuable networks of protected wilderness areas in Europe.